Soil Studies and Historical Archaeology: A Discussion on Forest Saami Settlements - Nina Karlsson (Current Swedish Archaeology, 2004)
This paper focuses on the historical Forest Saami culture in northem Swedcn. Since the time period in question is of historical date, it is possible to acquire information about the Forest Saami culture and way of life from both historical and ethnological records as well as archaeological records. The main purpose of this paper is to discuss how these different types of source material and different methods can be combined in order to study different aspects of Forest Saami settlements. The possibilities in studying decayed constructions and activity areas at Forest Saami settlements by means of soil chemical analysis are also discussed and exemplified.